PENGGUNAAN LKS UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR - Supriati Supriati (DIADIK, 2020)
Thepurpose  of  this  studyis  to  applythe  use  ofworksheets  to  increasestudent  activityand achievement.ThisresearchhasbeencarriedoutbymeansofaschoolactionresearchinSD Negeri 9Lahat.Thisresearchwasconductedinthreecyclestofindoutthattheuseofstudentworksheets toimprovestudentachievementresultsfromthe firstcycletothethird cycle.Thisprovesthatthe applicationoftheuseofworksheetsnotonly increasesstudentlearningactivitiesbutalsoincreases understanding ofthematerialandthishastheeffectofincreasing studentlearning outcomes.PTS takingtechniquesbymeansofobservationandtests,whiletheexperimentalclassonlytestedthe use of worksheetsthattookclass5c.Data analysiswas carriedoutwithsignificantsignificance using thet-test.Basedontheanalysisofthisresearchdata,itwasfoundthattherearedifferencesin learning modelsthatuseLKStoimprovestudentlearningactivitiesandachievementinsocial studies learning.Thepurpose  of  this  studyis  to  applythe  use  ofworksheets  to  increasestudent  activityand achievement.ThisresearchhasbeencarriedoutbymeansofaschoolactionresearchinSD Negeri 9Lahat.Thisresearchwasconductedinthreecyclestofindoutthattheuseofstudentworksheets toimprovestudentachievementresultsfromthe firstcycletothethird cycle.Thisprovesthatthe applicationoftheuseofworksheetsnotonly increasesstudentlearningactivitiesbutalsoincreases understanding ofthematerialandthishastheeffectofincreasing studentlearning outcomes.PTS takingtechniquesbymeansofobservationandtests,whiletheexperimentalclassonlytestedthe use of worksheetsthattookclass5c.Data analysiswas carriedoutwithsignificantsignificance using thet-test.Basedontheanalysisofthisresearchdata,itwasfoundthattherearedifferencesin learning modelsthatuseLKStoimprovestudentlearningactivitiesandachievementinsocial studies learning.